Tadek di e-Sabangan an expression of the people of Sabangan’s cultural identity and heritage through Takik and Tallibeng indigenous dances - Talangchey, Jessica C. (Philippine Journal of Science, 2023)
The indigenous dances of the e-Sabangan were passed down from one generation to the next and have been a part of their culture. A focus group discussion (FGD) with the participants of the study disclosed that the way the e-Sabangan move and communicate with their bodies is an expression of their way of life. This study aims to identify the indigenous dances prevalent in Sabangan, their purposes, representations, and implications to the e-Sabangan’s culture, health, and society in general. This study further aims to promote awareness and encourage the preservation of the e-Sabangan’s cultural heritage. There were 32 participants in this study composed of barangay officials, indigenous people’s mandatory representatives of Applai and Kankanaey indigenous peoples groups, and respected community elders of Sabangan, who have knowledge and understanding of the e-Sabangan’s culture and represent the 15 barangays of the municipality. Free, prior, and informed consent was secured from the National Commission on Indigenous Peoples before the conduct of the study. An FGD and prerecorded video documentation of the indigenous dances studied were utilized. Data were analyzed and interpreted based on thematic analysis. Results revealed that the Takik and Tallibeng dances are performed in various rituals, ceremonies, and occasions that serve essential functions such as community cleansing, thanksgiving, healing, and blessing. Such non-quotidian events are integrated with the e-Sabangan’s cultural practices which remain relevant in contemporary society. Moreover, cultural values are encapsulated in the various aspects of the dance such as the dance steps, attires, musical instruments, and chants. To promote and preserve these dances, it is essential to engage the community’s indigenous dance experts who can properly teach the Takik and Tallibeng to younger generations and encourage schools and institutions to provide an avenue wherein to heighten their interest in the e-Sabangan’s indigenous dances.